2009
DOI: 10.1111/j.1468-5906.2009.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

A Christian Cancellation of the Secularist Truce? Waning Christian Religiosity and Waxing Religious Deprivatization in the West

Abstract: Analysis of International Social Survey Program (ISSP) data collected in 18 Western countries in 1998 demonstrates that Christian desires for a public role of religion are strongest in countries where Christian religiosity is numerically most marginal. Moreover, Dutch data covering the period 1970-1996 confirm that the decline of the number of Christians in the Netherlands has been coincided by a strengthening of the call for public religion among the remaining faithful and by increased polarization about this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 33 publications
8
62
0
2
Order By: Relevance
“…It is measured by means of four Likert items that together yield a reliable scale (see Table 1). Figure 1 plots the percentage of non-Christians in each of the countries (x-axis) against the mean aspirations for religion's public revitalization among Christians in these countries (yaxis), which yields the same findings as those reported previously by Achterberg et al (2009). Christians (1998, N=18 countries, Pearson's r=0.72;p<0.001).…”
Section: Measurementsupporting
confidence: 72%
See 4 more Smart Citations
“…It is measured by means of four Likert items that together yield a reliable scale (see Table 1). Figure 1 plots the percentage of non-Christians in each of the countries (x-axis) against the mean aspirations for religion's public revitalization among Christians in these countries (yaxis), which yields the same findings as those reported previously by Achterberg et al (2009). Christians (1998, N=18 countries, Pearson's r=0.72;p<0.001).…”
Section: Measurementsupporting
confidence: 72%
“…Needless to say, then, such a finding would clearly contradict the notion that religious decline stimulates religion's public revitalization rather than its further privatization. This notion instead leads us to expect not only that Christian aspirations for religion's public revitalization are most typically found in the countries where Christian religion is least widespread (Hypothesis 1, which is identical to the hypothesis confirmed previously by Dekker (2007) and Achterberg et al (2009)), but also that these aspirations are not only found among older Christians, but just as much among younger ones (Hypothesis 2).…”
Section: Two Objections To the Notion Of Religion's Public Revitalizasupporting
confidence: 68%
See 3 more Smart Citations